Analisis Dampak Kebijakan Pengurangan Emisi Ghg Pada Kepatuhan Pengungkapan Sustainability Report Dan Praktik Akuntansi Lingkungan Perusahaan Indonesia - Dede Widiya; Azolla Degita Azis; Muhammad Anwar Masruri (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Global climate change caused by rising greenhouse gas (GHG) emissions is driving companies to improve transparency and accountability through sustainability reports and environmental accounting practices. In Indonesia, the energy sector is one of the sectors that contributes significantly to GHG emissions, and is therefore required to implement emission reduction policies and sustainability reporting in a more optimal manner. This study aims to analyze the impact of GHG emission reduction policies on compliance with sustainability report disclosures and environmental accounting practices among energy sector companies in Indonesia. This study employs a qualitative approach using a case study methodology. The study population consists of energy sector companies in Indonesia, while research informants were selected using purposive sampling, comprising sustainability managers, environmental managers, accounting staff, and the sustainability report drafting team. Research data consists of primary and secondary data obtained through semi-structured interviews, document reviews, sustainability reports, annual reports, and relevant regulations. Data analysis was conducted using qualitative analysis through the stages of data reduction, data presentation, triangulation, and drawing conclusions. The research findings indicate that GHG emission reduction policies drive the transformation of environmental accounting practices through the development of carbon accounting systems, the integration of environmental aspects into corporate decision-making, and improvements in the quality of sustainability report disclosures. However, policy implementation still faces various challenges, such as limitations in human resources, technology, and uniform environmental accounting standards. This study concludes that GHG emission reduction policies play a crucial role in improving environmental accounting practices and compliance with sustainability report disclosures among energy companies in Indonesia. The implications of this research highlight the need for enhanced corporate capacity, strengthened regulations, and the development of an integrated environmental reporting system to support corporate sustainability.